IOT Integration in Water Absorption of Sprout Growth System - Md Salleh, Salihatun (Journal of Advanced Research Design, 2025)
This research addresses the limitations of conventional mung bean sprout production methods by introducing an innovative, automated system. As small-scale sprout maker, current machine has non-stop watering, proves inefficient in regulating water and adversely affecting sprout growth. To counteract these shortcomings, the study presents an upgraded machine integrated IoT and systematic watering schedule. These setups involve varied mung bean quantities tested in sealed containers with controlled germination conditions. Over a two days period, the upgraded system demonstrates a comparable improvement in mung bean sprout growth parameters, evidenced by mung bean sprout growth and water absorption applying program watering system. Integrating the Internet of Things (IoT) through the Blynk platform facilitates real-time data analysis, adding dynamic understandings into environmental conditions. In conclusion, this study highlights the upgraded system’s execution, providing superior yield across various weight categories and emphasizing the role of advanced technology in optimizing agricultural machinery. The findings contribute substantively to discussions on technological enhancements emphasizing on the potential for water usage efficiency.